Long-term quality of life and functional outcomes in adults surgically treated for intramedullary spinal cord tumor - Tufo, Tommaso; Grande, Eleonora; Bevacqua, Giuseppina; Di Muccio, Ines; Cioni, Beatrice; Meglio, Mario; Ciavarro, Marco (Frontiers in Psychology, 2023)
Introduction Intramedullary spinal cord tumors (IMSCTs) are rare but clinically significant entities that may cause severe neurological decline with progressive pain and motor or sensory deterioration. Beyond the beneficial effects of surgical treatment and the long-term progression-free survival, neurological deficits may still persist after surgery, and information about the long-term patients' health-related quality of life (QoL) is still lacking. In this study, we investigate the patients' health perception 15 years after the surgery in an overall patients' wellbeing framework. Methods Patients surgically treated for IMSCT over a period from 1996 to 2011 were selected. After a mean of 15 years from the surgery, patient's self-administered questionnaire on disability, pain, sleep quality, and QoL was collected and neurological postoperative evaluation at the chronic stage was reexamined. Results Neurological deficits are reported in half of the patients in the postoperative chronic phase. After 15 years of surgery, half of the patients still report mild or severe disability grades associated with significantly higher pain and poor sleep and QoL. In accordance, the neurological condition measured at the chronic stage is significantly related not only to disease-specific symptoms (i.e., pain) but even to sleep quality complaints and poor QoL, measured at 15 years follow-up. Conclusions Health-related QoL is an important secondary outcome in patients. Although the progression-free survival, worse postoperative neurological conditions could predict long-term sequelae reflecting patients' poor health perception. It suggests the importance of preserving patients' functional status and globally evaluating patients' wellbeing to handle disease-specific symptoms but even more general aspects of QoL.